Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Thực hiện các phép tính:
a) 9,6.212−(2.125−1512):149,6.212−(2.125−1512):14
b) 518−1,456:725+4,5.45518−1,456:725+4,5.45;
c) (12+0,8−113).(2,3+4725−1,28)(12+0,8−113).(2,3+4725−1,28)
d) (−5).12:[(−14)+12:(−2)]+113(−5).12:[(−14)+12:(−2)]+113.
Hướng dẫn làm bài:
a) 9,6.212−(2.125−1512):149,6.212−(2.125−1512):14
=9,6.52−(250−1712)×4=9,6.52−(250−1712)×4
=4,8.5−(1000−173)=4,8.5−(1000−173)
=24−1000+173=24−1000+173
=−976+173=−976+173
=−97013=−97013
b) 518−1,456:725+4,5.45518−1,456:725+4,5.45;
=518−1,456×257+92.45=518−1,456×257+92.45
=518−0,208×25+185=518−0,208×25+185
=518−5,2+185=518−5,2+185
=25−468+32490=25−468+32490
=−11990=−11990
c) (12+0,8−113).(2,3+4725−1,28)(12+0,8−113).(2,3+4725−1,28)
=(12+45−43).(2310+10725−3225)=(12+45−43).(2310+10725−3225)
=(15+24−4030).(2310+10725−3225)=(15+24−4030).(2310+10725−3225)
=(15+24−4030).(115+214−6450)=(15+24−4030).(115+214−6450)
=−130.26550=−130.26550
=−53300=−53300
d) (−5).12:[(−14)+12:(−2)]+113(−5).12:[(−14)+12:(−2)]+113
=−60:[14+12×(−12)]+1.13=−60:[14+12×(−12)]+1.13
=−60:[−14−14]+113=−60:[−14−14]+113
=−60:(12)+113=−60:(12)+113
=120+113=120+113
=12113
a) \(9,6.2\dfrac{1}{2}-\left(2.125-1\dfrac{5}{12}\right):\dfrac{1}{4}\)
\(=9,6.\dfrac{5}{2}-\left(250-\dfrac{17}{12}\right).4\)
\(=4,8.5-\left(1000-\dfrac{17}{3}\right)\)
\(=24-1000+\dfrac{17}{3}\)
\(=-976+\dfrac{17}{3}=-970\dfrac{1}{3}\)
b) \(\dfrac{5}{18}-1,456:\dfrac{7}{25}+4,5.\dfrac{4}{5}\)
\(=\dfrac{5}{18}-1,456.\dfrac{25}{7}+\dfrac{9}{2}.\dfrac{4}{5}\)
\(=\dfrac{5}{18}-0,208.25+\dfrac{18}{5}\)
\(=\dfrac{5}{18}-5,2+\dfrac{18}{5}\)
\(=-\dfrac{119}{90}\)
c) \(\left(\dfrac{1}{2}+0,8-1\dfrac{1}{3}\right).\left(2,3+4\dfrac{7}{25}-1,28\right)\)
\(=\left(\dfrac{1}{2}+\dfrac{4}{5}-\dfrac{4}{3}\right).\left(\dfrac{23}{10}+\dfrac{107}{25}-\dfrac{32}{25}\right)\)
\(=-\dfrac{1}{30}.\dfrac{265}{50}=-\dfrac{53}{300}\)
d) \(\left(-5\right).12:\left[\left(-\dfrac{1}{4}\right)+\dfrac{1}{2}:\left(-2\right)\right]+1\dfrac{1}{3}\)
\(=-60:\left[\dfrac{1}{4}+\dfrac{1}{2}.\dfrac{-1}{2}\right]+1.\dfrac{1}{3}\)
\(=-60:\left[-\dfrac{1}{4}-\dfrac{1}{4}\right]+1\dfrac{1}{3}\)
\(=-60:\left(\dfrac{1}{2}\right)+1\dfrac{1}{3}\)
\(=121\dfrac{1}{3}\)
\(B=\frac{1-\frac{1}{\sqrt{49}}+\frac{1}{49}-\frac{1}{\left(7\sqrt{7}\right)^2}}{\frac{\sqrt{64}}{2}-\frac{4}{7}+\frac{2^2}{7^2}-\frac{4}{343}}\)
\(B=\frac{1-\frac{1}{7}+\frac{1}{49}-\frac{1}{343}}{\frac{8}{2}-\frac{4}{7}+\frac{4}{49}-\frac{4}{343}}\)
\(B=\frac{\frac{343}{343}-\frac{49}{343}+\frac{7}{343}-\frac{1}{343}}{4-\frac{4}{7}+\frac{28}{343}-\frac{4}{343}}\)
\(B=\frac{\frac{300}{343}}{\frac{28}{7}-\frac{4}{7}+\frac{24}{343}}\)
\(B=\frac{\frac{300}{343}}{\frac{24}{7}+\frac{24}{343}}\)
\(B=\frac{\frac{300}{343}}{\frac{1323}{343}+\frac{24}{343}}\)
\(B=\frac{300}{343}:\frac{1347}{343}\)
\(B=\frac{100}{449}\)
\(A=\frac{2^{12}.3^5-4^6.9^2}{\left(2^2.3\right)^6+8^4.3^5}-\frac{5^{10}.7^3-25^5.49^2}{\left(125.7\right)^3+5^9.14^3}\)
\(A=\frac{2^{12}.3^5-2^{12}.3^6}{2^{12}.3^6+2^{12}.3^5}-\frac{5^{10}.7^3-5^{10}.7^6}{5^9.7^3+5^9.2^3.7^3}\)
\(A=\frac{2^{12}.3^5\left(1-3\right)}{2^{12}.3^5.\left(3+1\right)}-\frac{5^{10}.7^3.\left(1-7^3\right)}{5^9.7^3.\left(1+8\right)}\)
\(A=\frac{-2}{4}-\frac{5.\left(-342\right)}{9}\)
\(A=\frac{-1}{2}+\frac{1710}{9}\)
\(A=\frac{-1}{2}+190\)
\(A=\frac{-1}{2}+\frac{380}{2}\)
\(A=\frac{379}{2}\)
\(A=16\dfrac{2}{7}:\left(\dfrac{-3}{5}\right)-28\dfrac{2}{7}:\left(\dfrac{-3}{5}\right)\)
\(A=\left(16\dfrac{2}{7}-28\dfrac{2}{7}\right):\left(\dfrac{-3}{5}\right)\)
\(A=\left(-12\right):\left(\dfrac{-3}{5}\right)\)
\(A=20\)
\(B=\left(\dfrac{3}{4}\right)^2-\left(\dfrac{7}{8}+3\right)+2.\left|\dfrac{-5}{8}\right|\)
\(B=\dfrac{9}{16}-\dfrac{31}{8}+2.\dfrac{5}{8}\)
\(B=\dfrac{9}{16}-\dfrac{31}{8}+\dfrac{5}{4}\)
\(B=\dfrac{-33}{16}\)
\(A=\dfrac{114}{7}:\left(\dfrac{-3}{5}\right)-\dfrac{198}{7}:\left(\dfrac{-3}{5}\right)\)
\(A=\left(\dfrac{114}{7}-\dfrac{198}{7}\right):\dfrac{-3}{5}\)
\(A=-12:\dfrac{-3}{5}\)
\(A=-12.\dfrac{-5}{3}\)
\(A=20\)
\(C=\left(\dfrac{3}{4}\right)^2-\left(\dfrac{7}{8}+3\right)+2.\left|\dfrac{-5}{8}\right|\)
\(C=\dfrac{9}{16}-\left(\dfrac{7}{8}+3\right)+2.\dfrac{5}{8}\)
\(C=\dfrac{9}{16}-\left(\dfrac{7}{8}+\dfrac{24}{8}\right)+2.\dfrac{5}{8}\)
\(C=\dfrac{9}{16}-\dfrac{31}{8}+2.\dfrac{5}{8}\)
\(C=\dfrac{9}{16}-\dfrac{31}{8}+\dfrac{5}{4}\)
\(C=\dfrac{9}{16}-\dfrac{62}{16}+\dfrac{5}{4}\)
\(C=\dfrac{-53}{16}+\dfrac{5}{4}\)
\(C=\dfrac{-53}{16}+\dfrac{20}{16}\)
\(C=\dfrac{-33}{16}\)
a. = \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}-\dfrac{-3}{8}\right\}\)
= \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}+\dfrac{3}{8}\right\}\)
= \(\dfrac{-1}{24}-\dfrac{5}{8}\)
= \(\dfrac{-2}{3}\)
b. = \(12\dfrac{7}{88}-3\dfrac{5}{11}\)
= \(8\dfrac{5}{8}\)
c. = \(\dfrac{-28}{9}+\dfrac{-413}{9}\)
= \(-49\)
d. = \(\dfrac{8}{35}:\dfrac{2}{11}+\dfrac{-8}{35}:\dfrac{2}{11}\)
= \(\dfrac{2}{11}:\left(\dfrac{8}{35}+\dfrac{-8}{35}\right)\)
= 0
5) \(\left(-2\right)^2+\sqrt{36}-\sqrt{9}+\sqrt{25}\)
=\(4+6-3+5\)
=\(12\)
2) \(\dfrac{11}{25}.\left(-24,8\right)-\dfrac{11}{25}.75,2\)
=\(\dfrac{11}{25}.\left(-24,8-75,2\right)\)
=\(\dfrac{11}{25}.\left(-100\right)\)
=\(-44\)
a)\(\frac{5}{3}\)+ \(\left(\frac{-2}{7}\right)\)-(-1,2)
=\(\frac{5}{3}+\left(\frac{-2}{7}\right)+\frac{6}{5}\)
=\(\frac{175+\left(-30\right)+126}{105}\)
=\(\frac{271}{105}\)
b) \(\frac{-4}{9}+\frac{-5}{6}-\frac{17}{4}\)
=\(\frac{-16+\left(-30\right)-153}{36}\)
=\(\frac{-199}{36}\)
\(\frac{5}{3}+\left(\frac{-2}{7}\right)-\left(\frac{-6}{5}\right)\)
=\(\frac{-2}{7}-\left(\frac{5}{3}+\frac{-6}{5}\right)\)
=\(\frac{-79}{105}\)\(\frac{-2}{7}-\frac{7}{15}\)
Bài 2:
a: =>x^2=60
=>\(x=\pm2\sqrt{15}\)
b: =>2^2x+3=2^3x
=>3x=2x+3
=>x=3
c: \(\Leftrightarrow\sqrt{\dfrac{1}{2}x-2}\cdot\dfrac{1}{2}=1\)
\(\Leftrightarrow\sqrt{\dfrac{1}{2}x-2}=2\)
=>1/2x-2=4
=>1/2x=6
=>x=12
a) \(\dfrac{1}{4}+\left(-\dfrac{3}{8}\right)=\dfrac{2}{8}+\left(-\dfrac{3}{8}\right)=-\dfrac{1}{8}\)
b)\(\dfrac{2^{10}.3^4}{3^5.2^8}=\dfrac{2^8.2^2.3^4}{3^4.3.2^8}=\dfrac{2^2}{3}=\dfrac{4}{3}\)
c) \(0,5.\sqrt{100}-\sqrt{\dfrac{1}{9}}=\dfrac{5}{10}.10-\dfrac{1}{3}=5-\dfrac{1}{3}=\dfrac{15}{3}-\dfrac{1}{3}=\dfrac{14}{3}\)
d) \(4\dfrac{5}{9}:\left(-\dfrac{5}{7}\right)+5\dfrac{4}{9}:\left(-\dfrac{5}{7}\right)\)
\(=\dfrac{41}{9}:\left(-\dfrac{5}{7}\right)
+\dfrac{49}{9}:\left(-\dfrac{5}{7}\right)\)
\(=\left(\dfrac{41}{9}+\dfrac{49}{9}\right):\left(-\dfrac{5}{7}\right)\)
\(=\dfrac{90}{9}:\left(-\dfrac{5}{7}\right)\)
\(=10:\left(-\dfrac{5}{7}\right)\)
\(=10.\left(-\dfrac{7}{5}\right)\)
\(=-14\)
\(\left(-8\dfrac{2}{5}\right):\left(-2\dfrac{4}{5}\right)=\dfrac{-42}{5}:\dfrac{-14}{5}=\dfrac{42}{14}=3\)